Annexin A6 regulates catabolic events in articular chondrocytes via the modulation of NF-κB and Wnt/ß-catenin signaling. - Takeshi Minashima; Thorsten Kirsch (PLoS ONE, 2018)
Annexin A6 (AnxA6) is expressed in articular chondrocytes at levels higher than in other mesenchymal cell types. However, the role of AnxA6 in articular chondrocytes is not known. Here we show that complete lack of AnxA6 functions resulted in increased ß-catenin activation in Wnt3a-treated murine articular chondrocytes, whereas AnxA6 expressing articular chondrocytes showed decreased ß-catenin activation. High expression of AnxA6 in human articular chondrocytes showed the highest inhibition of Wnt/ß-catenin signaling. Inhibition of Wnt/ß-catenin signaling activity by AnxA6 together with cytosolic Ca2+ was achieved by interfering with the plasma membrane association of the Wnt signaling complex. AnxA6 also affected the cross-talk between Wnt/ß-catenin signaling and NF-κB signaling by decreasing ß-catenin activity and increasing NF-κB activity in Wnt3a-, interleukin-1beta (IL-1ß)-, and combined Wnt3a/IL-1ß-treated cells. Wnt3a treatment increased the mRNA levels of catabolic markers (cyclooxygenase-2, interleukin-6, inducible nitric oxide synthase) to a much lesser degree than IL-1ß treatment in human articular chondrocytes, and decreased the mRNA levels of matrix metalloproteinase-13 (MMP-13) and articular cartilage markers (aggrecan, type II collagen). Furthermore, Wnt3a decreased the mRNA levels of catabolic markers and MMP-13 in IL-1ß-treated human articular chondrocytes. High expression of AnxA6 resulted in decreased mRNA levels of catabolic markers, and increased MMP-13 and articular cartilage marker mRNA levels in Wnt3a-treated human articular chondrocytes, whereas leading to increased mRNA levels of catabolic markers and MMP-13 in human articular chondrocytes treated with IL-1ß, or combined Wnt3a and IL-1ß. Our findings define a novel role for AnxA6 in articular chondrocytes via its modulation of Wnt/ß-catenin and NF-κB signaling activities and the cross-talk between these two signaling pathways.